Novel strategy for oral peptide delivery in incretin-based diabetes treatment. Issue 5 (10th August 2019) - Xu, Yining; Van Hul, Matthias; Suriano, Francesco; Préat, Véronique; Cani, Patrice D; Beloqui, Ana
Abstract : Objective: To fulfil an unmet therapeutic need for treating type 2 diabetes by developing an innovative oral drug delivery nanosystem increasing the production of glucagon-like peptide-1 (GLP-1) and the absorption of peptides into the circulation. Design: We developed a nanocarrier for the oral delivery of peptides using lipid-based nanocapsules. We encapsulated the GLP-1 analogue exenatide within nanocapsules and investigated in vitro in human L-cells (NCl-H716) and murine L-cells (GLUTag cells) the ability of the nanosystem to trigger GLP-1 secretion. The therapeutic relevance of the nanosystem in vivo was tested in high-fat diet (HFD)-induced diabetic mice following acute (one administration) or chronic treatment (5 weeks) in obese and diabetic mice. Results: We demonstrated that this innovative nanosystem triggers GLP-1 secretion in both human and murine cells as well as in vivo in mice. This strategy increases the endogenous secretion of GLP-1 and the oral bioavailability of the GLP-1 analogue exenatide (4% bioavailability with our nanosystem). The nanosystem synergizes its own biological effect with the encapsulated GLP-1 analogue leading to a marked improvement of glucose tolerance and insulin resistance (acute and chronic). The chronic treatment decreased diet-induced obesity, fat mass, hepatic steatosis, together with lower infiltration and recruitment of immune cell populations and inflammation. Conclusion: We developed a novel nanosystem compatible with human use that synergizes its own biological effect with the effects of increasing the bioavailability of a GLP-1 analogue. The effects of the formulation were comparable to the results observed for the marketed subcutaneous formulation. This nanocarrier-based strategy represents a novel promising approach for oral peptide delivery in incretin-based diabetes treatment.